The Role of Students' Critical Thinking Ability in Learning Mathematics with Problem Solving - Harahap, Vina Fauziah (EDUCTUM: Journal Research, 2023)
The purpose of this article is to discuss how learning mathematics through problem solving can develop students' critical thinking abilities. To achieve this goal, the method used is to describe how learning mathematics through problem solving can develop students' critical thinking skills based on research on supporting references. In the era of globalization, someone can obtain information in various ways, places and times. So that the information a person obtains is useful and does not have a negative impact, a "filter" is needed to filter all the information received. One of these filters is a person's critical thinking ability. Armed with critical thinking skills, an individual will carefully and deliberately determine/consider whether to accept, reject, or delay information. Because critical thinking skills are important, everyone should have them. One way to teach it is through learning mathematics, especially learning that uses problem solving methods. By participating in mathematics learning that uses problem solving methods, students are taught to use critical thinking skills at every stage, starting from understanding problems, designing solutions, implementing plans, to evaluating the results that have been achieved. By consistently being trained to use critical thinking skills in learning to solve mathematical problems, it is hoped that we can "develop" students' critical thinking skills.